The curricular organization by study situation (Revista Contexto & Educação, 2023)
It encourages us to understand which criteria are adopted by teachers/researchers in the elaboration and development of a curricular proposal by Study Situation (SE). For this, a qualitative research was carried out, through an unstructured interview with the creator of the SE. The interview recorded in audio, transcribed, and analyzed through The Discursive Textual Analysis, was guided by the following guiding question: how did the se proposal arise? With the experience you have and have had in this study and research journey with the SE, what are the main criteria considered in its elaboration and development? Much more than criteria for choosing themes and concepts, it was perceived that there are favorable conditions that mediated these choices and that may or may not influence their best success. Likewise, the contextual and normative conditions that permeated the origin of this se proposal, which coincides with the launch of PCNs, also show how difficult it is to organize the Science curriculum in the final stages of Basic Education in a contextualized way and in practice a teaching with effectively interdisciplinary characteristics.